An updating technique for finite elements models of existing high-rise buildings through ambient vibration tests - Villanueva, Luis I.
An enhanced procedure that integrates ambient vibration (AV) test and finite clement (FE) analysis results to improve the analytical model of existing high-rise buildings is developed. The natural frequencies and corresponding mode shapes derived from AV measurements are used as basis for updating the FE model of existing buildings. The basic idea is that these modal parameters are functions of the physical properties of the structures, hence can provide information about the "health" of the structure in-situ. A case study on an existing 12- story reinforced concrete (RC) building id conducted to assess the procedure developed. To illustrate the logistical constraints in practical situations, only five (5) vibration sensors are allocated.